1995
DOI: 10.1074/jbc.270.32.19120
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Amino-terminal Signal Peptide of the Cloned Rat Brain Na+-Ca2+ Exchanger Gene (RBE-1) Is Not Mandatory for Functional Expression

Abstract: The rat brain Na(+)-Ca2+ exchanger (RBE) gene, as well as other isoforms of this protein family, can be organized into 12 transmembrane alpha helices, the first of which was proposed by Durkin et al. (14) to constitute a cleavable signal peptide. We have prepared three amino-terminal mutants, in which 21, 26, and 31 amino acids beyond the initiating methionine were deleted. The deletions include the hydrophobic core of the putative signal peptide (N21), the entire putative signal peptide and parts of the putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Arg5 is located within the signal peptide sequence consisting of the first N-terminal 35 amino acids of NCX1, which are removed during biosynthesis (1). We expressed a mutant canine NCX1 with the Arg5Gln substitution in the fibroblastic cell line CCL39, and found that this mutant NCX1 was properly targeted into the plasma membrane and exhibited the normal Na /Ca 2 exchange activity (unpublished observations), consistent with previous reports stating that signal sequence is not essential for functional expression of the NCX1 protein (25,26). On the other hand, Arg703 is located within the large cytoplasmic loop connecting the transmembrane segments 5 and 6, which are not essential for the functional expression of the NCX1 protein (1).…”
Section: Discussionsupporting
confidence: 74%
“…Arg5 is located within the signal peptide sequence consisting of the first N-terminal 35 amino acids of NCX1, which are removed during biosynthesis (1). We expressed a mutant canine NCX1 with the Arg5Gln substitution in the fibroblastic cell line CCL39, and found that this mutant NCX1 was properly targeted into the plasma membrane and exhibited the normal Na /Ca 2 exchange activity (unpublished observations), consistent with previous reports stating that signal sequence is not essential for functional expression of the NCX1 protein (25,26). On the other hand, Arg703 is located within the large cytoplasmic loop connecting the transmembrane segments 5 and 6, which are not essential for the functional expression of the NCX1 protein (1).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, previous studies on the NCX1 molecule have indicated that, although not essential, M0 does play a role in optimal functional expression (37). Similarly, activity of NCKX3 in HEK293 cells was reduced when a clone lacking the M0 region was expressed.…”
Section: Discussionmentioning
confidence: 96%
“…(9). Preparation, testing, and purification of the antibodies was done as described (9,17). Goat anti-rabbit horseradish peroxidase-conjugated secondary antibody (Jackson ImmunoResearch Laboratories, Inc.) was used to detect antigen-antibody complexes using the ECL kit from Amersham Pharmacia Biotech.…”
Section: Inhibition Of Namentioning
confidence: 99%